Research on Candida dubliniensis in a Brazilian yeast collection obtained from cardiac transplant, tuberculosis, and HIV-positive patients, and evaluation of phenotypic tests using agar screening methods - Ribeiro, Patricia Monteiro [UNESP]; Rodrigues Querido, Silvia Maria; Back Brito, Graziella Nuernberg [UNESP]; Mota, Adolfo Jose; Koga-Ito, Cristiane Yumi [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP] (Elsevier B.V., 2011)
The aim of this study was to research Candida dubliniensis among isolates present in a Brazilian yeast collection and to evaluate the main phenotypic methods for discrimination between C. albicans and C. dubliniensis from oral cavity. A total of 200 isolates, presumptively identified as C. albicans or C. dubliniensis obtained from heart transplant patients under immunosuppressive therapy, tuberculosis patients under antibiotic therapy, HIV-positive patients under antiretroviral therapy, and healthy subjects, were analyzed using the following phenotypic tests: formation and structural arrangement of chlamydospores on corn meal agar, casein agar, tobacco agar, and sunflower seed agar; growth at 45 degrees C; and germ tube formation. All strains were analyzed by polymerase chain reaction (PCR). In a preliminary screen for C. dubliniensis, 48 of the 200 isolates on corn meal agar, 30 of the 200 on casein agar, 16 of the 200 on tobacco agar, and 15 of the 200 on sunflower seed agar produced chlamydoconidia; 27 of the 200 isolates showed no or poor growth at 45 degrees C. All isolates were positive for germ tube formation. These isolates were considered suggestive of C. dubliniensis. All of them were subjected to PCR analysis using C. dubliniensis-specific primers. C. dubliniensis isolates were not found. C. dubliniensis isolates were not recovered in this study done with immunocompromised patients. Sunflower seed agar was the medium with the smallest number of isolates of C. albicans suggestive of C. dubliniensis. None of the phenotypic methods was 100% effective for discrimination between C. albicans and C. dubliniensis. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: C. albicans; C. dubliniensis; Polymerase chain reaction; Phenotypic tests; Agar